The Role of Domestic and Foreign Investors in a Simple Model of Speculative Attacks - Diks, Cees (IMF Working Papers; Working Paper ;, 2005)
We introduce local and foreign investors in a simple model of speculative attacks. Local investors have less tolerance for overvaluation of the fixed exchange rate because they tend to incur lower costs when taking a short position and possess better information, and because of moral hazard created by discriminatory government guarantees. On the other hand, the prospect of higher taxation after a balance of payments crisis deters speculation by locals compared to foreign investors. Finally, the lower the degree of exchange rate pass-through, the more likely domestic investors are tp take the lead during capital flight.